Awareness of Risk Factors among Persons at Risk for Lung Cancer, Chronic Obstructive Pulmonary Disease and Sleep Apnea: A Canadian Population-Based Study - Shannon L Walker; David L Saltman; Rosemary Colucci; Lesli Martin (Canadian Respiratory Journal)
OBJECTIVE: To assess awareness among persons at risk for lung cancer, chronic obstructive pulmonary disease (COPD) and sleep apnea regarding symptoms and risk factors of the disease, and their attitudes regarding the disease and toward those who are affected.